Mediating role of information technology resources in new product development performance among Iranian businesses - Najafabadi, Fahimehsadat Ghorashi (2014)
The relationship between Information Technology (IT) and Business Performance (BP) is a recent and valuable research topic for both practitioners and students. To the best of the students’ knowledge, little research has been performed to analyze the direct contribution of IT to BP, and the existing findings were inconclusive in supporting this contribution. Viewed from IT-enabled organizational capability perspective, current IT researchers tend to consider the firm’s IT resources as complementary resources enhancing the value of other organizational capabilities and resources, which will further lead to the performance improvement. In fact, the study of the relationships between IT, organizational issues, and business performance is a cutting-edge research topic for IT scholars and practitioners and new IT enabled-organizational capabilities are being introduced continuously into the IT business value background. The purpose of this research is to examine how investment in different levels of IT resources can create IT competencies Cooperative Work Systems (CWS), Knowledge Management System (KMS) and Project and Resource Management System (PRMS), IT capabilities that farther create the higher order organizational capabilities of New Product Development (NPD) and Business Agility (BA). To examine the initial model, first a questionnaire-based survey was conducted and data was collected from Iranian business sectors. Then data analysis was performed by SEM technique (Structural Equation Modeling). Findings showed that investment in both technical and human IT resources and frequency of IT usage have positive effects on IT leveraging competence (in terms of CWS, KMS and PRMS). IT leveraging competence in turn converts the value of IT resources to organizational performance among Iranian companies by increasing NPD effectiveness and BA. Findings further demonstrated that the two higher order organizational capabilities of NPD effectiveness and BA are tangible to Iranian businesses, and their effective development can significantly enhance business performance in different dimensions.